Brand image, product quality, and price perception on drinking water purchase decision - Bangun, Rejeki (Enrichment : Journal of Management, 2023)
In a hypercompetitive global market, none of the business can survive without support from satisfied customers and loyal customers who buy goods or services. The purpose of this study was to analyze the effect of Brand Image, Product Quality, and Perceived Price on Purchasing Decisions for Sanford Drinking Water. The population of this research is the customers in the cafeteria of PT. Team Metal Indonesia, Batam totaling 112 people. The sample consists of 112 respondents, who were taken by the saturated sampling method. Data analysis using Multiple Regression and Hypothesis Testing. The results of this study concluded that Brand image has a significant effect on purchasing decisions of 0.045, product quality has a significant effect on purchasing decisions of 0.010, and the perceived price has a significant effect on purchasing decisions of 0.000. Brand image, product quality, and perceived price simultaneously influence the decisions purchase of 0.000